COMMUNITY-BASED TRAINING ON VISUAL COMMUNICATION MEDIA FOR GROWTH AND DEVELOPMENT MONITORING IN EARLY CHILDHOOD - aurora, Wahyu Indah Dewi; Syauqi, Ahmad; Delfira, Annisa; Kusdiyah, Erny; Darmawan, Armaidi; Hasmita, Debby (Universitas Jambi, 2025)
ABSTRACT Monitoring child growth and development at the community level is essential for the early detection of growth delays and developmental disorders. However, many Posyandu cadres still face difficulties in interpreting growth indicators due to limited technical training and the absence of effective visual media. This community service program aimed to improve the competence of Posyandu cadres in monitoring child growth and development through training on the use of visual aids. The program was implemented at the Tahtul Yaman Public Health Center, Jambi City, involving 30 cadres from 12 community health posts. The activities included needs assessment, development of flipcharts and posters, training and simulation sessions, field implementation, and evaluation. The results showed a significant improvement in cadres’ knowledge, with the mean score increasing from 55 (pre-test) to 82 (post-test), representing a 49% increase. Participant feedback indicated high satisfaction, and the use of visual aids facilitated better understanding and interaction during health education sessions. This program demonstrates that visual-based participatory training effectively enhances cadres’ knowledge, confidence, and communication skills, and can be replicated to strengthen community-based early detection and stunting prevention programs. Keywords: posyandu cadres, visual aids, child growth monitoring, community empowerment, stunting prevention ABSTRAK Pemantauan tumbuh kembang anak di tingkat komunitas sangat penting untuk deteksi dini keterlambatan pertumbuhan dan gangguan perkembangan. Namun, banyak kader Posyandu masih mengalami kesulitan dalam menginterpretasikan indikator tumbuh kembang karena keterbatasan pelatihan teknis dan tidak tersedianya media visual yang efektif. Program pengabdian kepada masyarakat ini bertujuan untuk meningkatkan kompetensi kader Posyandu dalam memantau tumbuh kembang anak melalui pelatihan penggunaan alat bantu visual. Kegiatan dilaksanakan di Puskesmas Tahtul Yaman, Kota Jambi, dengan melibatkan 30 kader dari 12 Posyandu aktif. Rangkaian kegiatan meliputi analisis kebutuhan, pengembangan flipchart dan poster, pelatihan serta simulasi, implementasi lapangan, dan evaluasi. Hasil menunjukkan adanya peningkatan signifikan pada pengetahuan kader, dengan nilai rata-rata meningkat dari 55 (pre-test) menjadi 82 (post-test), atau peningkatan sebesar 49%. Umpan balik peserta menunjukkan tingkat kepuasan yang tinggi, dan penggunaan media visual mempermudah pemahaman serta interaksi selama kegiatan edukasi kesehatan. Program ini membuktikan bahwa pelatihan partisipatif berbasis media visual efektif dalam meningkatkan pengetahuan, kepercayaan diri, dan keterampilan komunikasi kader, serta dapat direplikasi untuk memperkuat program deteksi dini dan pencegahan stunting berbasis masyarakat. Kata kunci: kader Posyandu, alat bantu visual, pemantauan tumbuh kembang, pemberdayaan masyarakat, pencegahan stunting